Obligatory CP Nominalization in Ndebele. (17th December 2018) - Pietraszko, Asia
Abstract: This article argues for the existence of obligatory clausal DP shells: a structure in which an embedded CP is directly dominated by a projection of D. While this structure has been proposed in previous literature, it poses a theoretical problem, since according to one theory of well‐formed extended projections, a D head can only occur in the extended projection of a noun (Grimshaw1991 2000 ). A careful investigation of embedded clauses in Ndebele—verb‐complement, noun‐complement, and relative clauses—points to the conclusion that the grammar must allow base generation of direct clausal DP shells.